Building A Training Program Based on The Deconstructive Approach To Acquiring Rhetorical Concepts Among University Students (Journal of the College of Basic Education, 2024)
This research aims to build a training program according to the deconstructive approach in acquiring rhetorical concepts among university students. To achieve the goal of the research, the researcher prepared a training program that included objectives, theoretical and applied content, appropriate teaching methods, accompanying activities, and educational means. The validity of the program was verified by presenting it to a group of arbitrators and experts using... The necessary statistical methods reach the following results:The research found a set of procedures that are believed to lead to the acquisition of rhetorical concepts among university students.In this research, the researcher came up with an integrated training program to acquire rhetorical concepts.In light of the research results, the researcher concluded the following:The weakness of university students in acquiring rhetorical concepts.The program, as a final form, is suitable for practical application based on the opinions of experts.In light of this, the researcher recommended the following recommendations:It has become necessary to pay attention to rhetorical concepts on the basis of critical analysis and the deconstructive approach.The necessity of using diverse and modern teaching methods with university students, especially in the subject of Arabic rhetoric.In continuation of the research, the researcher suggested the following:The program will be studied by a specialized committee in the Ministry of Higher Education in order to adopt it.Applying the program to a selected sample of university students in Arabic language departments.